2016
DOI: 10.1038/srep35947
|View full text |Cite
|
Sign up to set email alerts
|

Disabled-2 Determines Commitment of a Pre-adipocyte Population in Juvenile Mice

Abstract: Disabled-2 (Dab2) is a widely expressed clathrin binding endocytic adaptor protein and known for the endocytosis of the low-density lipoprotein (LDL) family receptors. Dab2 also modulates endosomal Ras/MAPK (Erk1/2) activity by regulating the disassembly of Grb2/Sos1 complexes associated with clathrin-coated vesicles. We found that the most prominent phenotype of Dab2 knockout mice was their striking lean body composition under a high fat and high caloric diet, although the weight of the mutant mice was indist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 64 publications
(92 reference statements)
0
13
0
Order By: Relevance
“…Indeed, a role of Dab2 in suppressing Ras/MAPK activation accounts for embryonic development (Yang et al, 2009) and several physiological phenotypes observed in Dab2 null mice (Tao et al, 2014, 2016b). Probably, the activity as a negative regulator of the Ras/MAPK pathway contributes to the tumor suppressor activity of Dab2 as well.…”
Section: Dab2 In the Regulation Of Cellular Signaling Pathwaysmentioning
confidence: 99%
See 4 more Smart Citations
“…Indeed, a role of Dab2 in suppressing Ras/MAPK activation accounts for embryonic development (Yang et al, 2009) and several physiological phenotypes observed in Dab2 null mice (Tao et al, 2014, 2016b). Probably, the activity as a negative regulator of the Ras/MAPK pathway contributes to the tumor suppressor activity of Dab2 as well.…”
Section: Dab2 In the Regulation Of Cellular Signaling Pathwaysmentioning
confidence: 99%
“…In a high fat and caloric feeding experiment that was to investigate cholesterol metabolism, an unexpected observation was that the Dab2 null mice were resistant to high fat diet-induced weight gain (Tao et al, 2016b). The most prominent phenotype of Dab2 knockout mice was their striking lean body composition under a high fat and high caloric diet, although the weight of the mutant mice was indistinguishable from wild-type littermates on a regular chow.…”
Section: Roles Of Dab2 In Adipocyte Differentiationmentioning
confidence: 99%
See 3 more Smart Citations